2005
DOI: 10.1007/s00259-005-1888-7
|View full text |Cite
|
Sign up to set email alerts
|

Radiation exposure to family members of patients with thyrotoxicosis treated with iodine-131

Abstract: The radiation dose to family members of thyrotoxic patients treated with up to 600 MBq of radioiodine is well below recommended dose constraints if EC instructions are given and compliance is adequate. The duration of restrictions for various age groups used in this study may be considered when establishing guidelines in Norway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…There have been reports of family members who received radiation doses greater than the safety level [5,7]; however, there has been no report of any patient who developed a thyroid malignancy after third-party iodine-131 exposure. Although strong cause-effect relationship could not be demonstrated on a single-case evidence, our reported case emphasizes that care should be taken in giving ambulatory radioactive iodine therapy to a patient having young family members.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…There have been reports of family members who received radiation doses greater than the safety level [5,7]; however, there has been no report of any patient who developed a thyroid malignancy after third-party iodine-131 exposure. Although strong cause-effect relationship could not be demonstrated on a single-case evidence, our reported case emphasizes that care should be taken in giving ambulatory radioactive iodine therapy to a patient having young family members.…”
Section: Discussionmentioning
confidence: 89%
“…A multicenter study of outpatient radioiodine therapy in UK found that 6 of 17 family members aged 3 years or younger who were children of the patients received radiation at an adjusted dose of more than 1 mSv, while almost all adult family members received an adjusted dose within the safety limits [5]. A recent case series from Norway also reported one 2-year-old child who absorbed a radiation dose of 3.04 mSv from the mother despite repeatedly being informed of the safety instructions [7]. It should be noted that the mother of the latter case received only 260 MBq of radioactive iodine, which was comparable with the mother of our patient.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…10 -14 Similar results were reported in other studies on hyperthyroidism or thyroid cancer outpatient treatment, with all reported mean values attaining less than 1.0 mSv. [15][16][17][18][19] Although caregiver thyroid glands were not surveyed with a radiation detector in this study, radiation exposure from contamination or radioiodine intake seems to have been much lower than external exposure. This was also shown by other researchers, 19,20 -22 and thoroughly discussed in a previous study by our group.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 concludes that in all studies the excretion rate of 131 I activity from patients is more than 75% within 72 hours of activity administration. Figure 1 shows the Table 2 shows the radiation dose levels to family members/ caregivers of radioiodine patient which pointed out that the doses to masses in various studies [4,[30][31][32][33][34][35][36][37][38] including current report were in the magnitude of annual limit to general public (1mSv) which wrapping up that the patients treated with 131 I do not share a significant radiation dose to the public [4,16,39]. Table 3 presents the data of patients' stay at hospital including current study.…”
Section: Discussionmentioning
confidence: 99%